Intracardiac Ectopic Thyroid Tissue: A Case Report - Hira Nasir; Azra Bashir; Faria Waqar Khan; Aribah Atiq; Akhtar Sohail Chughtai (University of Lahore, 2024)
We present the case of a 36-year-old female who visited the OPD of a local hospital in Lahore, Pakistan, with history of chest pain, shortness of breath and palpitations. Echocardiogram and transesophageal echocardiography revealed right ventricular outflow tract mass, dilated coronary sinus and atrial septal defect. Surgery was advised, and successful excision of the mass was done and the specimen later sent to Chughtai Institute of Pathology for histopathological evaluation and diagnosis. The results revealed benign thyroid tissue with no evidence of malignancy. The patient was symptom-free on follow up after 6 months.